Financial Distress, Earnings Management, and Leverage Effect on Firm Value with Firm Size as a Moderation Variable - Agustina, Enica; Malau, Melinda (Ridwan Institute, 2023)
The study is aimed to analyze whether financial distress, earnings management, and leverage affects a firm value with firm size as a moderation variable. The method used in this study is multiple linear analysis. Samples engaged 144 public companies in manufacturing sectors listed in Indonesia Stock Exchange (Bursa Efek Indonesia) period 2017-2021. The result of the research revealed that earnings management positively affected firm value, firm size strengthened the relationship between financial distress with firm value, and firm size strengthened the relationship between earnings management and firm value. The study implies that companies can manage their resources and provide project financial statements based on applicable accounting standards to increase firm value. Furthermore, investors and creditors can consider the prospect of business and future projections of the issuer's fundamentals